Genetic and functional analyses do not explain the association of high PRC1 expression with poor survival of breast carcinoma patients - Brynychová, Veronika; Ehrlichová, Marie; Hlaváč, Viktor; Fürstová, Vlasta; Pecha, Václav; Levá, Jelena; Trnková, Markéta; Mrhalová, Marcela; Kodet, Roman; Vrána, David; Kovar, Jan; Václavíková, Radka; et al. (Biomedicine & pharmacotherapy, 2016)
Microtubules are vitally important for eukaryotic cell division. Therefore, we evaluated the relevance of mitotic kinesin KIF14, protein-regulating cytokinesis 1 (PRC1), and citron kinase (CIT) for the prognosis of breast carcinoma patients. Transcript levels were assessed by quantitative real-time PCR in tissues from two independent groups of breast carcinoma patients and compared with clinical data. Tissue PRC1 protein levels were estimated using immunoblotting, and the PRC1 tagged haplotype was analyzed in genomic DNA. A functional study was performed in MDA-MB-231 cells in vitro. KIF14, PRC1, and CIT transcripts were overexpressed in tumors compared with control tissues. Tumors without expression of hormonal receptors or high-grade tumors expressed significantly higher KIF14 and PRC1 levels than hormonally-positive or low-grade tumors. Patients with high intra-tumoral PRC1 levels had significantly worse disease-free survival than patients with low levels. PRC1 rs10520699 and rs11852999 polymorphisms were associated with PRC1 transcript levels, but not with patientś survival. Paclitaxel-induced PRC1 expression, but PRC1 knockdown did not modify the paclitaxel cytotoxicity in vitro. PRC1 overexpression predicts poor disease-free survival of patients with breast carcinomas. Genetic variability of PRC1 and the protein interaction with paclitaxel cytotoxicity do not explain this association.
Keywords: Cell Death; messenger RNA; regulace genové exprese u nádorů; nádory prsu; proteiny buněčného cyklu; lidé; paclitaxel; Cell Cycle Proteins; Breast Neoplasms; Kaplan-Meier Estimate; Gene Expression Regulation, Neoplastic; studie případů a kontrol; buněčná smrt; Female; Polymorphism, Genetic; RNA, Messenger; polymorfismus genetický; Disease-Free Survival; Gene Knockdown Techniques; ženské pohlaví; Case-Control Studies; Humans; Kaplanův-Meierův odhad; nádorové buněčné linie; přežití bez známek nemoci; Paclitaxel; genový knockdown; Cell Line, Tumor